Building models of knowledge management strategies in private higher education: analytical research in a group of private - Abdullah, Hatem Ali; Rahim, Muhammad Yaseen; Ali, Jihad Hamid (International Journal of Psychosocial Rehabilitation, 2020)
The research dealt with the analysis of building a model for knowledge management strategies in private higher education, therefore a group of Iraqi private colleges (the Dijlah University College, AL-ESRAA University College, and Al-Kitab University) was chosen in the research, relying on positivist philosophy to derive its hypotheses and the deductive approach to test it, however, the research population representing by (1110) individuals was distributed by (263, 590 and 257) respectively for the three colleges, and a non-random (intentional) sample of (258) individuals was chosen using the statistical methods of Herbert Arken to represent the community correctly, the exploratory factor analysis was used to examine the main research hypothesis. The research found that there are three strategies for knowledge management in the research colleges and that these strategies have explained 50% of the total variance, which means that there are other strategies that have not been researched or may be due to other factors not included in the model and that the strategy of maintaining the current situation has gained importance among other strategies, and this may be due to the nature of the Iraqi environment, Accordingly, the research recommended that colleges should be given the freedom to choose their orientations and business models and not to resort to imitation and simulation to public universities, as well as interest in development and innovation through contracting with foreign universities and achieving twinning between universities.